Primera descripción del nido y movimientos estacionales del Birro Chico (Pyrrhomyias c. cinnamomea) en Argentina - Ortiz, Diego; Ferro, Ignacio; Barrionuevo, Carlos (Nuestras Aves, 2012)
Este artículo no cuenta con un resumen.